Microstructure and Piezoelectric Properties of Lead-Free (K0.5Na0.5)NbO3-LiNbO3-SrTiO3 Ceramics. Issue 1 (2nd January 2016) - Zhang, Yang; Li, Lingyu; Bai, Wangfeng; Zhai, Jiwei
Abstract : (1−x)[0.93(K0.5 Na0.5 )NbO3 -0.07LiNbO3 ]-xSrTiO3 ((1-x)KNN-LN-xST) system ceramics with ABO3 structure were synthesized by conventional solid state reaction route and investigated to differentiate the effects of polymorphic phase transition. The crystal structure of (1-x)KNN-LN-xST ceramics was changed from orthorhombic to tetragonal at x≥0.04, then became a morphotropic phase boundary in which both the orthogonal and tetragonal phases coexisted at 0.04<x<0.08, and was converted to tetragonal structure at x≥0.08. At phase boundary, the dielectric and piezoelectric properties of these ceramics change obviously. The Curie temperature decreased with increasing of x in the temperature range from 200°C to 400°C.The polymorphic phase transition between the orthorhombic and tetragonal phases plays a very important role in enhancement of the piezoelectric properties of (1-x)KNN-LN-xST ceramics.